2012
DOI: 10.1094/pdis-04-12-0377-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Distribution of Acidovorax avenae subsp. avenae Associated with Creeping Bentgrass Etiolation and Decline

Abstract: Giordano, P. R., Chaves, A. M., Mitkowski, N. A., and Vargas, J. M., Jr. 2012. Identification, characterization, and distribution of Acidovorax avenae subsp. avenae associated with creeping bentgrass etiolation and decline. Plant Dis. 96:1736-1742.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Acidovorax has been mostly considered as biotrophic pathogen [11]. However, bacteria of this genus are also known as commensal species or plant beneficial bacteria, which produce secondary metabolites and hormones promoting plant growth, as well as competing with pathogens [12].…”
Section: Introductionmentioning
confidence: 99%
“…Acidovorax has been mostly considered as biotrophic pathogen [11]. However, bacteria of this genus are also known as commensal species or plant beneficial bacteria, which produce secondary metabolites and hormones promoting plant growth, as well as competing with pathogens [12].…”
Section: Introductionmentioning
confidence: 99%
“…The second group is formed by the plant-pathogenic species A. anthurii, A. avenae and A. konjaci (Willems & Gillis, 2015). Acidovorax avenae consists of three subspecies (avenae, cattleyae and citrulli) that cause a wide range of economically important diseases in monocotyledonous and dicotyledonous plants (Giordano et al, 2012;Willems & Gillis, 2015). However, these three subspecies have different host ranges.…”
Section: Introductionmentioning
confidence: 99%
“…cattleyae infects only orchid species belonging to the genera Cattleya and Phalaenopsis. Aaa has a wide host range in the Poaceae family, including maize, rice, sorghum, oats, barley, rye, various millets, vasey grass and sugarcane (Martin & Wismer, 1989;Song et al, 2003;Fontana et al, 2013;Willems & Gillis, 2015), as well as tea (Schaad et al, 2008), white bird of paradise (Strelitzia nicolai; Seijo & Peres, 2011) and creeping bentgrass (Agrostis stolonifera; Giordano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Decline includes chlorosis and necrosis that can lead to severe thinning throughout the turfgrass stand (Latin, 2012). Recent reports show that bacteria ( Acidovorax avenae and Xanthomonas translucens ) are causal agents in etiolation (Giordano et al, 2012; Roberts et al, 2014). Acidovorax species cause bacterial brown stripe of creeping bentgrass ( Agrostis stolonifera L.) (CBG) turf in Japan (Furuya et al, 2009), and Giordano et al (2012) observed that infection by Acidovorax avenae subsp.…”
mentioning
confidence: 99%
“…etiolation (Giordano et al, 2012;Roberts et al, 2014). Acidovorax species cause bacterial brown stripe of creeping bentgrass (Agrostis stolonifera L.) (CBG) turf in Japan (Furuya et al, 2009), and Giordano et al (2012) observed that infection by Acidovorax avenae subsp. avenae resulted in etiolation and tip dieback.…”
mentioning
confidence: 99%